Evaluation of biomass and lipid yield using different cultivation regimes in Scenedesmus sp. (Research, Society and Development, 2022)
The search for renewable sources of biofuels is growing every day. As an example, we have biodiesel, a non-fossil fuel that can totally or partially replaces petroleum diesel without the need for adaptation. Microalgae can be used as raw material to produce biodiesel due to its growth rate and for having high lipid yields, in addition to its great capacity to develop in different environments. The use of microalgae to produce biofuels can be a potential and economical alternative in relation to other fuel sources. In addition to the high content of lipids and carbohydrates, they show rapid growth and high efficiency in fixing CO2. Thus, this work aimed to cultivate the microalgae Scenedesmus sp. in different regimes, analyzing the best conditions to produce bio-oil. The tests were carried out varying the culture medium, light, reactor, days of cultivation and aeration of the environment, totaling 16 tests. After carrying out the experiment was decided that the best microalgae cultivation regime aiming at a percentage of oil was using an inoculum of 20% of the useful volume in a horizontal reactor, with CHU culture medium and maximum light intensity with three “light” lamps how daylight, and duration of 30 days, with aeration and without vitamins addition. The associated effects of aeration, luminosity, cultivation time and growth medium, had a greater influence on the production of lipids.